Rome re-imagined twelfth-century Jews, Christians and Muslims encounter the Eternal City - Hamilton, Louis I.; Riccioni, Stefano (Leiden ; Boston : Brill, 2011)
This collection examines the image of Rome through Arabic, Greek, Hebrew, Latin, and Persian descriptions of the eternal city. Placing the twelfth-century renaissance into a Mediterranean context. The city of Rome is revealed as a multi-vocal object of desire and a contested ideal.
Description based upon print version of record.
Includes bibliographical references and index.
Keywords: Rome (Italy) -- History -- 476-1420.; Rome (Italy) -- Church history; Rome (Italy) -- In literature; Rome (Italy) -- In art; Jews -- Italy -- Rome -- History -- To 1500.; Christians -- Italy -- Rome -- History -- To 1500.; Muslims -- Italy -- Rome -- History -- To 1500.; Papacy -- History -- To 1500.; Civilization, Medieval -- Classical influences; Travelers' writings -- History and criticism; Christians -- Italy -- Rome -- History -- To 1500.; Civilization, Medieval -- Classical influences; Jews -- Italy -- Rome -- History -- To 1500.; Muslims -- Italy -- Rome -- History -- To 1500.; Papacy -- History -- To 1500.; Rome (Italy) -- Church history; Rome (Italy) -- History -- 476-1420.; Rome (Italy) -- In art; Rome (Italy) -- In literature; Travelers' writings -- History and criticism; History; Social Science; SOCIAL SCIENCE / Discrimination & Race Relations; SOCIAL SCIENCE / Minority Studies; Electronic books